2016
DOI: 10.3892/ijo.2016.3805
|View full text |Cite
|
Sign up to set email alerts
|

Matrine suppresses invasion of castration-resistant prostate cancer cells by downregulating MMP-2/9 via NF-κB signaling pathway

Abstract: Matrine is an alkaloid from Sophora flavescens that exhibits multiple protective effects on cancers. However, the molecular mechanisms of anti-metastatic effects of matrine on castration-resistant prostate cancer (CRPC) remain unknown. This study investigated the anti-metastatic effects of matrine on CRPC to identify the underlying mechanisms. The effects of matrine on the cell viability of DU145 and PC-3 cells were measured using MTS assay. The impact of matrine on expression levels of matrix metalloproteinas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 36 publications
(47 reference statements)
3
30
0
Order By: Relevance
“…KEGG pathway analysis of 1240 common differential genes revealed the top 10 enriched pathways related to integrin, apoptosis, angiogenesis, platelet‐derived growth factor (PDGF), P53, Wnt, vascular endothelial growth factor (VEGF), PI3 kinase, p38/MAPK, and cell cycle (Figure B). Our previous results show a close relationship between matrine and cell apoptosis so that genes related apoptosis were selected to be further analyzes (Figure C).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…KEGG pathway analysis of 1240 common differential genes revealed the top 10 enriched pathways related to integrin, apoptosis, angiogenesis, platelet‐derived growth factor (PDGF), P53, Wnt, vascular endothelial growth factor (VEGF), PI3 kinase, p38/MAPK, and cell cycle (Figure B). Our previous results show a close relationship between matrine and cell apoptosis so that genes related apoptosis were selected to be further analyzes (Figure C).…”
Section: Resultsmentioning
confidence: 99%
“…Other studies have shown that matrine can block cell cycle in G1 phase, S phase, or G2/M period . The observed synergistic impacts may be caused by either promoting the expression of GADD45B gene or through other signaling pathways such as EGFR/ERK/MMP‐2, AKT/GSK3β/β‐catenin, and PTEN/AKT to inhibit tumor cell progression . It is unknown whether matrine will promote or inhibit autophagy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such inhibition on colorectal cancer cells was also observed when treated with 2,3,5,4′-tetrahydroxystilbene-2-O-β-D-glucoside [49]. As an alkaloid derived from Sophora flavescens, matrine can inhibit the invasion and migration of castration-resistant prostate cancer DU145 and PC3 cells by suppressing MMP-9 and MMP-2 expressions through NF-κB pathway [50]. The phenol derived from Taiwanese edible fungus Antrodia cinnamomea, 2,3,5-trimethoxy-4-cresol, was recently described as an effective antimetastatic agent against lung cancer via suppressing Akt, MMP-2 and MMP-9, and increasing E-cadherin and TIMP-1 [51].…”
Section: Suppression Of Proteases Expressionmentioning
confidence: 81%
“…Researches have pointed out MAT can conspicuously restrain prostate carcinoma. 13 In addition, a research has pointed out that MAT restrains the activity of BC cells. 14 Many types of researches have pointed out that the development of malignant carcinomas usually results from abnormal gene expression.…”
Section: Introductionmentioning
confidence: 99%